Median effective dose of remimazolam combined with sufentanil for inhibiting laryngeal mask airway insertion responses in children of different ages - Hongyun Li; Jinxia Wang; Rong Wei; Yan Jiang (Frontiers in Pharmacology)
IntroductionWe determined the median effective dose and 95% confidence interval (CI) of remimazolam required to inhibit laryngeal mask airway (LMA) insertion reactions combined with sufentanil 0.3 μg/kg in pediatric anesthesia.MethodsChildren scheduled to undergo elective laryngeal mask anesthesia were divided into the preschool (age: 3–6 years) and school-age (6–12 years) groups. The timer was started after intravenous remimazolam was administered; thereafter, 0.3 μg/kg sufentanil was injected intravenously. The laryngeal mask was placed 3 min after remimazolam was finished. If a positive response to LMA insertion, such as movement, swallowing, coughing, hiccups, or other reactions, was observed during the insertion, the dose was increased by 0.03 mg/kg for the next patient; if there was no response, the dose was decreased by 0.03 mg/kg instead. The trial officially commenced after the first LMA was successfully inserted and continued until alternating positive and negative responses formed seven crossover points. Thereafter, probit regression was performed to calculate the median effective dose (ED50) and 95% effective dose (ED95) with the corresponding 95% CIs. The time from remimazolam administration to the disappearance of the eyelash reflex was recorded. Heart rate and mean arterial pressure were recorded before (T1, baseline values) and 3 min after (T2) intravenous remimazolam administration. Adverse reactions were also noted.ResultsOverall, 52 children were included; 25 belonged to the preschool group and 27 to the school-age group. In the preschool group, the ED50 and ED95 for remimazolam and their 95% CIs were 0.476 (0.447–0.517) mg/kg and 0.554 (0.515–0.688) mg/kg, respectively. In the school-age group, the ED50 and ED95 for remimazolam and corresponding 95% CIs were 0.427 (0.399–0.463) mg/kg and 0.504 (0.467–0.635) mg/kg, respectively. The dosage for the preschool group was significantly higher than that for the school-age group (p = 0.003). Conversely, the time from remimazolam administration to the disappearance of the eyelash reflex; LMA insertion success rate; or incidence of coughing, movement, swallowing, and hiccups did not differ significantly between the two groups.ConclusionRemimazolam can be safely used for laryngeal mask anesthesia induction in pediatric patients.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400087333.